Control of Rattail Fescue (Vulpia myuros) in No-Till Winter Wheat. (September 2014) - Lawrence, Nevin C.; Burke, Ian C.
Abstract : Rattail fescue is a problematic weed for small grain producers in the Pacific Northwest when no-till production practices are used. Pyroxsulam and pyroxasulfone are two herbicides not previously evaluated for control of rattail fescue. Pyroxasulfone provided levels of control (> 74%) similar to flufenacet. Pyroxsulam did not consistently control (21 to 71%) rattail fescue. Rattail fescue biomass was reduced by pyroxasulfone and flufenacet compared to the nontreated control. Effective consistent rattail fescue control was only achieved where PRE herbicides were used. When managing rattail fescue, PRE herbicides pyroxasulfone and flufenacet plus metribuzin are essential components of an integrated management strategy.